The Mast Cell Is an Early Activator of Lipopolysaccharide-Induced Neuroinflammation and Blood-Brain Barrier Dysfunction in the Hippocampus - Yiwei Wang; Huanhuan Sha; Leting Zhou; Yinan Chen; Qin Zhou; Hongquan Dong; Yanning Qian (Mediators of Inflammation)
Neuroinflammation contributes to or even causes central nervous system (CNS) diseases, and its regulation is thus crucial for brain disorders. Mast cells (MCs) and microglia, two resident immune cells in the brain, together with astrocytes, play critical roles in the progression of neuroinflammation-related diseases. MCs have been demonstrated as one of the fastest responders, and they release prestored and newly synthesized mediators including histamine, β-tryptase, and heparin. However, temporal changes in MC activation in this inflammation process remain unclear. This study demonstrated that MC activation began at 2 h and peaked at 4 h after lipopolysaccharide (LPS) administration. The number of activated MCs remained elevated until 24 h after LPS administration. In addition, the levels of histamine and β-tryptase in the hippocampus markedly and rapidly increased within 6 h and remained higher than the baseline level within 24 h after LPS challenge. Furthermore, mast cell-deficient KitW-sh/W-sh mice were used to investigate the effects of MCs on microglial and astrocytic activation and blood-brain barrier (BBB) permeability at 4 h after LPS stimulation. Notably, LPS-induced proinflammatory cytokine secretion, microglial activation, and BBB damage were inhibited in KitW-sh/W-sh mice. However, no detectable astrocytic changes were found in WT and KitW-sh/W-sh mice at 4 h after LPS stimulation. Our findings indicate that MC activation precedes CNS inflammation and suggest that MCs are among the earliest participants in the neuroinflammation-initiating events.